AKTIVITAS FISIK TERHADAP PENURUNAN KADAR GULA DARAH PASIEN DM TIPE II TAHUN 2022 - Siti Ayu Fatimah Subarja; Zahrah Maulidia Septimar; H. A. Y. G. Wibisono (Nusantara Hasana Journal, 2022)
Diabetes Mellitus (DM) is a group of metabolic diseases characterized by high levels of glucose in the blood (hyperglycemia) due to the effects of insulin secretion, insulin action, or a combination of both. In type II of DM, the body is able to produce insulin but becomes resistant so that insulin cannot work effectively. Purpose to review physical activity on reducing blood sugar levels in patients with type II diabetes mellitus. A literature review was conducted on articles obtained from a number of three databases, such as Google Scholar, PubMed, and Scopus with the keywords diabetes mellitus, physical activity. Some of articles that were found showed that physical activity